First record of a critically endangered species, European sturgeon Acipenser sturio, in the stomach of harbor porpoises Phocoena phocoena from the North Sea - Heße, Eileen; Gessner, J.; Siebert, Ursula; Gilles, Anita (Endangered Species Research, 2024)
The European sturgeon Acipenser sturio has been of substantial commercial interest in the past. Today it is considered Critically Endangered, with only one remaining population in Europe. Fulfilling national conservation strategies and aiming for the conservation of biological diversity, Germany has released European sturgeons into their former habitats (Elbe River and its tributaries) as part of experimental measures to restore the population. However, little is known about their biology, sensitivity of life-stages to threats or trophic interactions within their former habitats. Here, we report on the first known predation of reintroduced sturgeons by harbor porpoises Phocoena phocoena and discuss predator-prey interactions in the light of sturgeon conservation. Stomach content analysis on stranded harbor porpoises revealed remains (scutes; modified ganoid scales) of European sturgeon in stomachs of 2 adult harbor porpoises (1.23%). Mean ± SD back-calculated lengths of ingested sturgeons were 26.11 ± 1.90 and 26.49 ± 1.93 cm, respectively, based on dorsal scute morphometrics. To date, no predator-prey interactions between sturgeons and harbor porpoises have been recorded in the North Sea. Future research into the diet of aquatic top predators with overlapping habitats at stocking sites of European sturgeons, transcending national boundaries, will uncover possible conservation concerns, conflicts of species-specific management interests and reintroduction success of European sturgeons.